Evaluation of SNA001, a Novel Recombinant Human Thyroid Stimulating Hormone Injection, in Patients With Differentiated Thyroid Carcinoma - Gu, Yushen; Xu, Hongrong; Yang, Yanling; Xiu, Yan; Hu, Pengcheng; Liu, Min; Wang, Xiangqing; Song, Jun; Di, Yan; Wang, Jian; Zhang, Xiaoxia; Xu, Tao; et al. (Frontiers in Endocrinology, 2021)
SNA001 is a novel recombinant human thyroid stimulating hormone (rhTSH). rhTSH has long been approved in several countries to facilitate monitoring and ablation of thyroid carcinoma without hypothyroidism caused by thyroid hormone withdrawal (THW). To assess the safety, tolerance, pharmacokinetics and pharmacodynamics properties of SNA001, the two-period (SNA001 period and THW period), dose-ascending study in well-differentiated thyroid cancer (DTC) patients was designed.Three doses (0.45 mg, 0.9 mg, and 1.35 mg) of SNA001 were intramuscularly injected, twice in the SNA001 period to stimulate iodine-131 uptake and thyroglobulin (Tg) release. Twenty-four hours after the last dose of SNA001, iodine-131 (111 185MBq) was administrated, followed by whole-body scan (WBS) 48 hours later. THW period began just after SNA001 washout and lasted for about 3 6 weeks. When TSH level was above 30 mU/L, iodine-131 (111 185MBq) was administrated, followed by a WBS and Tg detection 48 hours later.Twenty-four DTC patients after thyroidectomy were enrolled, mean peak concentrations of SNA001 in 0.45 mg, 0.9 mg, 1.35 mg groups were 18.5, 26.7, and 37.0 ng/mL (about 244.7, 354.2 and 489.6 mU/L) respectively, within 28 32 hours after first dose of SNA001. SNA001 was metabolized in a dose-dependent manner. The results of WBS and Tg release in the SNA001 period were compared with those in THW period. Compared to Tg level in baseline, the Tg levels in SNA001 and THW periods were increased, with 78% of subjects showing higher Tg levels in the THW period. 100% of the patients had concordant qualitative results of the scans within two periods in three groups. Symptoms of hypothyroidism were relieved in the SNA001 period compared with THW period, though there was no significant difference in most of the scale scores. There were no serious adverse events related to SNA001, the most common adverse event were gastrointestinal symptoms, of mild and transient nature.Thus, SNA001 promises to be a safe and effective method to stimulate iodine-131 uptake and Tg secretion during monitoring and ablation for DTC without the disadvantages of incidental hypothyroidism.